OPTIMALISASI KESIAPSIAGAAN PRAJURIT KODIM 0101/BS DALAM PENANGGULANGAN BENCANA DI BANDA ACEH - Gayoni, Taqwaddin, Yanis (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
Abstract: This study aims to analyze the preparedness of human resources of Military District Command Command (KODIM) 0101 / BS so as to have adequate skills and skills in improving disaster preparedness in order to overcome natural disasters, analyzing obstacles and obstacles in preparation effort KODIM 0101 / BS in disaster management in Banda Aceh, and analyzed efforts to increase the preparedness of KODIM 0101 / BS soldiers in disaster management in Banda Aceh. The population used in this research is all KODIM 0101 / BS soldiers. The sample was taken as many as 82 people. Data collection was done by distributing questionnaires to respondents and in-depth interviews and documentation. Data analysis technique performed in this study by calculating the questionnaire distributed to soldiers KODIM 0101 / BS using the formula percentage and index preparedness. Based on the results of data analysis can be explained the preparedness of soldiers KODIM 0101 / BS Banda Aceh in terms of disaster management is very ready, it is obtained with the average value of variable preparedness is 89. TNI also has provided knowledge and attitude about preparedness in tackling disaster trained in particular. In order to maintain TNI soldiers' preparedness in tackling disasters, specialist training programs and knowledge dissemination of disaster mitigation will be needed to hone and maintain the capability of warrior preparedness especially in the case of disaster management.Keywords: Optimization, Preparedness, DisasterAbstrak: Penelitian ini bertujuan untuk menganalisis kesiapan sumber daya manusia Prajurit Komando Distrik Militer (KODIM) 0101/BS sehingga memiliki keahlian dan keterampilan yang memadai dalam meningkatkan kesiapsiagaan menghadapi bencana dalam rangka upaya penanggulangan bencana alam, menganalisis kendala dan hambatan dalam upaya kesiapsiagaan prajurit KODIM 0101/BS dalam penanggulangan bencana di Banda Aceh, dan menganalisis upaya peningkatan kesiapsiagaan prajurit KODIM 0101/BS dalam penanggulangan bencana di Banda Aceh. Populasi yang dipakai dalam penelitian ini adalah seluruh prajurit KODIM 0101/BS. Sampel penelitian diambil sebanyak 82 orang. Pengumpulan data dilakukan dengan penyebaran kuisioner kepada responden dan wawancara mendalam serta dokumentasi. Teknik analisis data yang dilakukan dalam penelitian ini dengan menghitung kuisioner yang dibagikan kepada prajurit KODIM 0101/BS menggunakan rumus presentase dan indeks kesiapsiagaan. Berdasarkan hasil analisis data dapat dijelaskan kesiapsiagaan prajurit KODIM 0101/BS Banda Aceh dalam hal penanggulangan bencana sudah sangat siap, hal ini diperoleh dengan nilai rata-rata dari variable kesiapsiagaan adalah 89. TNI juga telah dibekali ilmu dan sikap tentang kesiapsiagaan dalam menanggulangi bencana yang dilatih secara khusus. Untuk mempertahankan kesiapsiagaan prajurit TNI dalam menanggulangi bencana juga perlu diterapkan program pelatihan khusus dan sosialisasi pengetahuan mitigasi bencana untuk mengasah dan mempertahankan kemampuan kesiapsiagaan prajurit khususnya dalam hal penanggulangan bencana.Kata Kunci: Optimalisasi, Kesiapsiagaan, Bencana